EVALUASI STIMULASI PENGASAMAN (MATRIX ACIDIZING) RESERVOIR PADA SUMUR FFS DI LAPANGAN PT PERTAMINA EP CEPU FIELD ZONA 11 - Ferinda F Salhuteru; Henk Subekti; Berthy Pelasula (Journal Mechanical Engineering, 2025)
As time goes by, FFS well production has decreased. This then became the background for implementing matrix-type acidification stimulation measures in the relevant fields. The acid used in FFS wells is 15% HCl and 6% HF. Significantly, this acidification process has 3 stages that need to be applied, namely, preflush, mainflush, and postflush. After this stimulation, it is estimated that there will be an increase of 26.5% with an oil price of 50 USD per bbl. After evaluation, it seems clear that there has been an increase in the production rate considering that the two compounds have reacted on a scale as seen in the increase in Q price in the FFS tang well, from 147 BOPD to 200 BOPD. From an economic perspective, we can also see efficiency in the use of equipment because it minimizes many aspects that need to be changed, in other words the production rate increases only with basic capital for certain chemicals. From the evaluation carried out, economic indicators can also be seen which make this research much more economical compared to previous research, where the FFS Well has a gross profit (Gross Revenue) of 8316000 USD. Meanwhile, the net profit obtained reached 3992000 USD. The NPV value with a discount of 11.87% is 477.58 USD, with an IRR of 33,79693377% and a POT of approximately 4.48 years. Keywords: Production rate, FFS well, scale, matrix, acidizing.